Cemitérios Amazônicos: um estudo sobre os espaços funerários do Estado do Amapá - Séculos XXXXI - Silva , Tiago Varges da (2024)
The history of the cemeteries of the state of Amapá, built throughout the twentieth century and the beginning of the twenty-first century, as well as their sepulchral and tomb complex and the funeral rituals developed in these spaces, is the central theme of this thesis. Therefore, the Ritual of Castilho and the Ritual of Illumination of the Dead comprise the objects of analysis of the research. A diversity of cemetery typologies, such as public, riverside, quilombola, and Israeli cemeteries forms Amapá's cemeteries. The constitution of these funerary spaces is linked to the historical processes of colonization and occupation of the territory of Amapá. We propose to understand the origins of these cemeteries and their relations with such historical and social movements, which contributed to the formation of the state of Amapá and, consequently, its funerary culture. These Amazonian funerary spaces, except Israeli cemeteries, are formed for a plurality of tombs, characterized by their vernacular art, quite diversified in the use of materials such as wood and masonry, used in the construction of their architecture and adornment. Among the various tomb typologies found in these cemeteries, the modality of castilho tombs is the most unique and representative of the Amapá’s cemeteries. The castilhos are pre-molded tombs placed in graves, both of adults and children, amid a ritual practiced in several cemeteries in Amapá. Based on a photographic survey carried out between 2016 and 2024, we propose an analysis of the cemetery typologies and tomb categories, analyzing the history of these spaces. In this way, the construction of the Amapá’s cemeteries was analyzed from the historical perspective throughout the formation of the state of Amapá. The results of the research demonstrated that the Amapá’s cemeteries, in addition to being funerary spaces indispensable in the daily life of practice, are also fundamental historical, social, and cultural records through which it is possible to tell the story of the formation of several Amapá cities.